2020
DOI: 10.1002/emp2.12129
|View full text |Cite
|
Sign up to set email alerts
|

Limiting the number of open charts does not impact wrong patient order entry in the emergency department

Abstract: Objective We sought to examine the impact of limiting the number of open active charts on wrong patient order entry events among 13 emergency departments (EDs) in a large integrated health system. Methods A retrospective chart review of all orders placed between September 2017 and September 2019 was conducted. The rate of retract and reorder events was analyzed with no overlap in both the period pre‐ and post‐intervention period. Secondary analysis of error rate by clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The study of Canfield et al (2020) reported error event rates per thousand order sessions for restricted and unrestricted conditions of 2.2/1000 and 2.4/1000, respectively. They reported the total number of order session instances across the entire study ( n = 5,988,914), but did not give the subtotals for the two conditions and hence could not be included in computing a pooled effect size for all studies.…”
Section: Methodsmentioning
confidence: 99%
“…The study of Canfield et al (2020) reported error event rates per thousand order sessions for restricted and unrestricted conditions of 2.2/1000 and 2.4/1000, respectively. They reported the total number of order session instances across the entire study ( n = 5,988,914), but did not give the subtotals for the two conditions and hence could not be included in computing a pooled effect size for all studies.…”
Section: Methodsmentioning
confidence: 99%
“…While this solution showed early promise, recent studies have found that limiting the number of open charts made no significant difference in the number of wrong-patient orders. [26][27][28] Prior studies have also identified HIT enhancements to improve identification of wrong-patient errors in radiology. One study implemented radiopaque patient identification stickers as an additional check to ensure the patients' conditions correlated with their imaging, and a second study involved capturing photographs of patients' faces simultaneously with portable chest radiographs.…”
Section: Wrong-patient Errors During Orderingmentioning
confidence: 99%